Style as a topical category of modern musicology and music education - Govorukhina, Nataliya; Smyrnova, Tetiana; Polska, Iryna; Sykhlenko, Iryna; Savelieva, Ganna (Babeș-Bolyai University, 2021)
The aim of the work is to arrange the scientific achievements on the category of “musical performing style” and identify mechanisms for practical testing of theoretical provisions in the pedagogical activities of higher musical education institutions. The research methodology is based on a combination of general scientific and musicological approaches, in particular: system approach hermeneutic, historical, comparative, genre-style, interpretive method, as well as performance analysis. The results of the study indicate that domestic art schools were formed by synthesizing several national and historical style traditions. Music and performance schools were actively developing in parallel with the compositional work in Ukraine in the second half of the twentieth century; the work of representatives of those schools presents a fairly wide range of style research. A natural result of the studied problem of musical performing style should be its transfer to the practical plane of professional education of musicians and performers, formation of musical style competence in students. Kotlyarevsky Kharkiv National University of Arts was selected as an experimental platform for its formation. During 2019-2021, a pedagogical experiment continued to test the formation of musical and style thesaurus, performance and intellectual skills, professionally important qualities of music students. In the context of studying of different styles in the system of musical performance by the students of higher music education institutions, it is important that the art of music is constantly evolving and new directions and trends in music styles emerge almost every day in Ukraine and the world as a whole. This undoubtedly makes the need for further research on this issue urgent (usually with the use of advanced domestic and foreign experience in music education).
Keywords: Музичний стиль, музикознавство сучасне, перформанс музичний, перформативний стиль музичний, освіта музична